THEORETICAL FEASIBILITY OF COLD FUSION ACCORDING TO THE BSM - SUPERGRAVITATION UNIFIED THEORY: THEORETICAL FEASIBILITY OF COLD FUSION ACCORDING TO THE BSM - SUPERGRAVITATION UNIFIED THEORY - Sargoytchev, Stoyan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Advances in the field of cold fusion or LENR in which the energy release cannot be explained by a chemical process, need a deeper understanding of the nuclear reactions and, more particularly, the possibility for modification of the Coulomb barrier. The treatise “Basic Structures of Matter – Supergravitation Unified Theory”, suggests non spherical shapes of the protons and neutrons. Held by strong nuclear forces they form atomic nuclei as fractal three-dimensional structures. Such nuclear structures exhibit an excellent match to the pattern of Periodic Table, showing signatures of valences, Pauli exclusion principle and angular restrictions of the chemical bonds. The Coulomb barrier in these nuclear structures does not converge to a small size as in the case of the Bohr planetary model and it could be modified by some technical methods. Using the suggested atomic models, the analysis of some successful cold fusion experiments resulted in practical considerations for modification of the Coulomb barrier.